Assessment of changes in tumor heterogeneity following neoadjuvant chemotherapy in primary esophageal cancer. Issue 2 (1st March 2015) - Yip, C.; Davnall, F.; Kozarski, R.; Landau, D. B.; Cook, G. J. R.; Ross, P.; Mason, R.; Goh, V.
Summary: To assess the changes in computed tomography (CT) tumor heterogeneity following neoadjuvant chemotherapy in esophageal cancer. Thirty-one consecutive patients who received neoadjuvant chemotherapy for esophageal cancer were identified. Analysis of primary tumor heterogeneity (texture) was performed on staging and post-chemotherapy CT scans. Image texture parameters (mean grey-level intensity, entropy, uniformity, kurtosis, skewness, standard deviation of histogram) were derived for different levels of image filtration (0–2.5). Proportional changes in each parameter following treatment were obtained. Comparison between pathological tumor response and texture parameters was analyzed using Mann–Whitney U -test. The relationship between CT texture and overall survival) was estimated using the Kaplan–Meier method. Tumor texture became more homogeneous after treatment with a significant decrease in entropy and increase in uniformity (filter 1.0 and 2.5). Pretreatment (filter 1.5, P = 0.006) and posttreatment standard deviation of histogram (filter 1.0, P = 0.009) showed a borderline association with pathological tumor response. A proportional change in skewness <0.39 (filter 1.0) was associated with improved survival (median overall survival 36.1 vs. 11.1 months; P < 0.001). CT tumor heterogeneity decreased following neoadjuvant chemotherapy and has the potential to provide additional information in primary esophageal cancer.